Delegation and Product Differentiation - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1993)
The effects of the delegation of control to managers are investigated in a duopolistic market for differentiated goods. It appears that delegation is profitable to shareholders under Cournot competiton, provided that the rival firm maximizes profit.
Keywords: 330